ChemInform Abstract: Synthesis, Characterization and Antimicrobial Screening of Some Novel Chalcones and Their Derivatives. Issue 12 (14th March 2013) - Chate, Asha V.; Joshi, Ratnadeep S.; Mandhane, Priyanka G.; Gill, Charansingh
Abstract A new series of novel chalcones (III) is synthesized and transformed into chromenone derivatives (IV) and (V) via oxidative cyclization reactions.